Quelle est l’influence des négociations d’entreprise sur la structure des salaires? - Rusinek, Michael; Rycx, François (Bruxelles, 2008)
"In many European countries, the majority of workers have their wages directly defined by industry-level agreements. In addition, for some workers, industry agreements are complemented by firm-specific agreements. This paper provides a critical survey of the literature on effects of this two-tier bargaining system on the structure of wages in Europe and more particularly in Belgium. Empirical findings almost always show that firm-level agreements have a positive and significant effect on workers’ wages. The impact on the dispersion of wages, however, is ambiguous. This may be due to the use of different data and methodologies but also to national differences. In particular, the degree of centralisation of collective bargaining appears to be a key variable."